Compassion focused therapy for self-stigma and shame in autism: a single case pre-experimental study - Riebel, Marie; Krasny-Pacini, Agata; Manolov, Rumen; Rohmer, Odile; Weiner, Luisa (Frontiers in Psychiatry, 2024)
Exposure to public stigma can lead to the internalization of autism-related stigma (i.e., self-stigma), associated with negative health, occupational and social outcomes. Importantly, self-stigma is linked to shame and social isolation. Although elevated self-stigma has been reported in autistic adults, to the best of our knowledge, interventions designed to target this issue are lacking. Compassion is an effective way to reduce the emotional correlates of self-stigma (i.e., shame) and their impacts on mental health. However, no study has investigated whether compassion focused therapy (CFT) can effectively reduce self-stigma in autistic adults. The present study aims at investigating whether and how self-compassion improvement following CFT may reduce self-stigma and shame in an autistic individual. A single case pre-experimental design (SCED) was used with weekly repeated measures during four phases: (i) pure baseline without any intervention (A), (ii) case conceptualization (A'), (iii) intervention (B) where CFT was delivered, (iv) follow-up without intervention (FU). The participant is a 46-year-old autistic man with high self-stigma and shame. Self-report measures of self-compassion and self-stigma and a daily idiographic measure of shame were used. There was a large increase in self-compassion between pure baseline (A) and the intervention phase (A'B) (Tau-U = 0.99), maintained at follow-up. Similarly, there was a moderate decrease of selfstigma (Tau-U = 0.32). In contrast, when we compared the whole baseline phase AA' (i.e. considering the conceptualisation phase as baseline) to the intervention (B), there was no change in self-stigma (Tau-U = -0.09). There was no change in self-stigma between the intervention (B) and follow-up (Tau-U = -0.19). There was a moderate decrease in daily shame reports between the baseline (AA') and the intervention (B) (Tau-U = 0.31) and a moderate decrease between the pure baseline (A) and intervention (A'B) (Tau-U=0.51). CFT was feasible for this autistic client and our results show that CFT led to the improvement of self-compassion. Changes on self-stigma measures were moderate. Self-stigma may need more time to change. Because self-stigma is involved in poorer social functioning and mental health in autistic adults, our results are promising and suggesting conducting more large-scale studies on CFT in autistic adults.